The role of endothelial dysfunction in the formation of complications during interventional procedures - Aksenov, E. V.; Golovenko, V. B. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The work deals with the role of endothelial dysfunction in the formation of complications during interventional procedures. From the entire data (1680 patients with coronary heart disease), were selected 156 patients – 71 patients with different complications during diagnostic and therapeutic interventional coronary procedures and 85 consecutive patients who had no registered complications. Age of surveyed was 66,96±1,81 years. Among them – 104 men and 52 women. In addition to routine clinical indicators of registration of patients, the target examination included determination of endothelial function (nitrate levels in plasma and red blood cells, the L-arginine, the number of desquamated endothelial (DE) in the blood plasma). During the work has identified a strong positive correlation between the type of percutaneous coronary intervention and the degree of change in the level of DE, which was most expressed during percutaneous transluminal coronary angioplasty. Manifestation of indicators of endothelial dysfunction in the form of increased levels of ED was more pronounced in patients with unstable angina form.